2007
DOI: 10.1080/00498250601149206
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP3A4*18B polymorphisms with the pharmacokinetics of cyclosporine in healthy subjects

Abstract: The aim of this study is to evaluate the association of the CYP3A4*18B genotype with the cyclosporine metabolism in healthy subjects. We employed PCR-RFLP assays for analysis of the CYP3A4*18B genotype. Each of 26 subjects, comprising 12 CYP3A4*1/*1, 12 CYP3A4*1/*18B and 2 CYP3A4*18B/*18B, was given a single oral dose of cyclosporine (4 mgkg(-1)). The plasma concentrations of cyclosporine were measured for up to 24 h post dose by high-performance liquid chromatography-electrospray mass spectrometry. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 22 publications
4
35
2
Order By: Relevance
“…The CYP3A4*18B polymorphism was identified to be associated with significant variability in fentanyl consumption 48 h following radical gastrectomy in Chinese Han patients. This polymorphism was previously found at high frequencies in Asian populations (9,10). The CYP3A4*18B mutant allele frequency is 28.4% in patients of this study, consistent with previous reports of 24.9% in 416 Japanese individuals (9), 22.7% in 176 Chinese patients undergoing lower abdominal surgery (11) and 26.9% in 143 Chinese gynecological patients (12).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The CYP3A4*18B polymorphism was identified to be associated with significant variability in fentanyl consumption 48 h following radical gastrectomy in Chinese Han patients. This polymorphism was previously found at high frequencies in Asian populations (9,10). The CYP3A4*18B mutant allele frequency is 28.4% in patients of this study, consistent with previous reports of 24.9% in 416 Japanese individuals (9), 22.7% in 176 Chinese patients undergoing lower abdominal surgery (11) and 26.9% in 143 Chinese gynecological patients (12).…”
Section: Discussionsupporting
confidence: 81%
“…This discrepancy may, in part, be explained by variations in surgery types (upper vs. lower abdominal surgery), small sample size [97 (present study) and 79 (22) vs. 176 (11) and 143 (12) patients], analgesic formula [fentanyl only vs. fentanyl + droperidol (11,12)] and additional unknown factors. By contrast, Hu et al (10) reported that the CYP3A4*18B genotype significantly affects cyclosporine pharmacokinetics and is likely to result from higher enzymatic activity associated with this mutation. Results of both previous studies and the present study indicate that the CYP3A4*18B variant allele may be critical for polymorphic CYP3A4 enzymatic activities and thus variations in the consumption of fentanyl.…”
Section: Oprm1 A118g Cyp3a4*18b -------------------------------------mentioning
confidence: 95%
See 2 more Smart Citations
“…A series of studies examined the relationship between the CYP3A4*1G polymorphism and drug metabolism but resulted in inconsistent findings [32][33][34] . In agreement with our observation, CYP3A4*1G was not associated with cyclosporine concentrations in 126 renal recipients [27] ; however, Qiu et al [22] and Hu et al [35] found that it was associated with a lower CsA concentration. Differences in study populations, sample size, ethnicities and particularly in the duration after transplantation might be possible confounding factors.…”
Section: Discussionsupporting
confidence: 81%